Sphero-conical spiral antenna - Lukyanchikov, A. V.; Salazko, V. N.; Evstigneev, I. A. (Видавництво Національного університету "Львівська політехніка", 2009)
The mathematical model of radiation characteristics of the sphero-conical helical antenna in the form of extending conductors is offered. This model allows not only to simplify an essentially calculation, but the analysis of similar structures. The results of theoretical and experimental research of the sphero-conical helical antenna are also discussed in the paper.
Keywords: sphero-conical helical antenna; mathematical model; radiation characteristics; polar pattern